Implementasi Metode Fuzzy Sugeno Pada Embedded System Untuk Mendeteksi Kondisi Kebakaran Dalam Ruangan - Rezak Andri Purnomo; Dahnial Syauqy; Mochammad Hannats Hanafi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Fire is an event caused more by human error. In this final project there are 3 sensors namely MQ-2 sensor, DHT11 sensor, and flame sensor connected with Arduino Mega 2560 microcontroller. Arduino Mega 2560 Microcontroller embedded fuzzy sugeno logic as the output decision based on fuzzy calculation. There are 3 fuzzy processes, namely fuzzification process, inference process, and defuzzification process. Fuzzification process using 3 variables are smoke, temperature, and fire variables. Each variable has a fuzzy membership set. Variable smoke has 3 set that is tenuous, medium, and concentrated. Variablel temperature has 4 set that is cold, cool, warm, and hot. Variable fire has 4 sets that is close to the sensor, rather close to the sensor, away with the sensor, and no fire. Defuzzification process using the MIN-MAX method, then each variable output conditions will be searched for the largest value (MAX). From the test results, the system can determine the various conditions of the room with 100% accuracy. The average system execution time is Â± 417.4 ms. In fuzzy testing obtained percentage of success of 100%. This indicates that the system can work well in determining the condition of the room based on the input of the sensor. Keywords: fire, sensor MQ-2, DHT11 sensor, flame sensor, arduino mega 2560, fuzzy sugeno